(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This annotation examines preventive medical care during early pregnancy and strategies for reducing associated risks. Early pregnancy is a critical period that significantly affects maternal and fetal health. Prenatal complications, such as miscarriage, preterm labor, gestational hypertension, and gestational diabetes, can arise if proper preventive care is not provided.